Characterization of NAD+/NADP+-Specific Isocitrate Dehydrogenases From Oleaginous Fungus Mortierella alpina Involved in Lipid Accumulation - Tang, Xin; Sun, Xiaoqi; Wang, Xuxu; Zhang, Hao; Chen, Yong Q.; Zhao, Jianxin; Chen, Haiqin; Chen, Wei (Frontiers in Nutrition, 2021)
Mortierella alpina has a strong capacity for lipid accumulation. Isocitrate dehydrogenase (IDH) plays an important role in affecting the flow of intracellular carbon sources and reducing power NADPH for lipid biosynthesis. In this study, the effect of various IDHs (NAD+- and NADP+-specific) in M. alpina on the lipid accmulation was investigated through homologous overexpression. The results showed that the transcription level and enzyme activity of the IDHs from M. alpina (MaIDHs) in homologous overexpressing strains were higher than those of the control strain, but that their biomass was not significantly different. Among the various NAD+-specific MaIDH1/2/3 overexpression, NAD+-MaIDH3 reduced total lipid content by 12.5%, whereas overexpression NAD+-MaIDH1 and NAD+-MaIDH2 had no effect on fatty acid content. Intracellular metabolites analysis indicated that the overpression NAD+-MaIDH3 strain had reduced the fatty acid accumulation, due to its greater carbon flux with the tricarboxylic acid cyle and less carbon flux with fatty acid biosynthesis. For the NADP+-MaIDH4/5/6 recombinant strains overexpressing only NADP+-MaIDH4 enhanced the total fatty acid content by 8.2%. NADPH analysis suggested that this increase in lipid accumulation may have been due to the great reducing power NAPDH is produced in this recombinant strain. This study provides theoretical basis and guidance for the analysis of the mechanism of IDH function and the potential to improve lipid production in M. alpina.